Invasive fungal infections in children with rheumatic diseases - O. P. Kozlova; M. M. Kostik; M. D. Kuznetsova; M. F. Dubko; L. S. Snegireva; A. L. Shavkin; E. A. Ligostaeva; O. L. Kopchak; S. M. Ignatieva; T. S. Bogomolova; N. N. Klimko (Журнал инфектологии, 2021)
Introduction. In children with rheumatic diseases, severe fungal infections (invasive mycoses – IM) are not well understood.Objectives. To analyze risk factors, disease course of IM in children with systemic rheumatic diseases.Materials and methods. For diagnosis of IM were used criteria EORTC/MSGERC, 2019. We reviewed the literature over the past 15 years on IM in children with rheumatic diseases from the international databases Pubmed and Web of Science.Results. In retrospective multicenter study were included 8 children with IM and systemic rheumatic diseases: ANCA-associated vasculitis (n=4), systemic lupus erythematosus (n=3), juvenile rheumatoid arthritis (n=1). Median age was 13,5 (8-17) y., boys – 67%. Invasive aspergillosis was diagnosed in 5 patients and invasive candidiasis – 3. The risk factors of invasive mycoses were high rheumatic disease activity (100%), corticosteroids (prednisolone ≥ 0,3 mg/kg/d) use for ≥21 d (87,5%), immunosuppressive therapy (87,5%), recent (≤ 2 weeks) pulse steroid therapy (75%), hemophagocytic lymphohistiocytosis (62,5%), prolonged (≥ 10 days) severe neutropenia (≤ 0,5х109/l) (62,5%), and prolonged (≥10 days lymphopenia (≤ 1,0х109/l) (37,5%). In patients with invasive aspergillosis the involved organ was the lung, in patients with invasive candidiasis a candidemia was diagnoses. All patients received antifungal therapy. The overall 30 days survival rate was 37,5%.Сonclusions. Children with high rheumatic diseases activity and intensive treatment with immunosuppressive agents should be considered as patients with a high risk of invasive mycoses with a high mortality.